Parallel computing techniques for interferometric sonar based imaging - Mohamed Fazil Mohamed Firdhous. (2008)
This research work presents a novel method for the determination of phase delay, which is based on Residue Number Systems (RNS) arithmetic. It has been shown that, by incorporating RNS, a high degree of parallelism could be introduced within the unwrapping process. This provides for the realization of a high-speed architecture to compute the required phase delay.